Effects of stand structure and ungulates on understory vegetation in managed and unmanaged forests. Issue 3 (15th March 2022) - Chevaux, Laura; Mårell, Anders; Baltzinger, Christophe; Boulanger, Vincent; Cadet, Serge; Chevalier, Richard; Debaive, Nicolas; Dumas, Yann; Gosselin, Marion; Gosselin, Frédéric; Rocquencourt, Agnès; Paillet, Yoan
Abstract: Conventional conservation policies in Europe notably rely on the passive restoration of natural forest dynamics by setting aside forest areas to preserve forest biodiversity. However, since forest reserves cover only a small proportion of the territory, conservation policies also require complementary conservation efforts in managed forests in order to achieve the biodiversity targets set up in the Convention on Biological Diversity. Conservation measures also raise the question of large herbivore management in and around set‐asides, particularly regarding their impact on understory vegetation. Although many studies have separately analyzed the effects of forest management, management abandonment, and ungulate pressure on forest biodiversity, their joint effects have rarely been studied in a correlative framework. We studied 212 plots located in 15 strict forest reserves paired with adjacent managed forests in European France. We applied structural equation models to test the effects of management abandonment, stand structure, and ungulate pressure on the abundance, species richness, and diversity of herbaceous vascular plants and terricolous bryophytes. We showed that stand structure indices and plot‐level browsing pressure had direct and opposite effects on herbaceous vascular plant species diversity; these effects were linked with the light tolerance of the different species groups. Increasing canopy cover had an overall negative effect on herbaceous vascular plant abundance and species diversity. The effect was two to three times greater in magnitude than the positive effects of browsing pressure on herbaceous plants diversity. On the other hand, a high stand density index had a positive effect on the species richness and diversity of bryophytes, while browsing had no effect. Forest management abandonment had few direct effects on understory plant communities, and mainly indirectly affected herbaceous vascular plant and bryophyte abundance and species richness and diversity through changes in vertical stand structure. Our results show that conservation biologists should rely on foresters and hunters to lead the preservation of understory vegetation communities in managed forests since, respectively, they manipulate stand structure and regulate ungulate pressure. Their management actions should be adapted to the taxa at stake, since bryophytes and vascular plants respond differently to stand and ungulate factors.